Assessment of Air Pollution and its Impact on Human Health Behavior in Jhansi City, Uttar Pradesh, India - Sharma2, Rambir Singh1, L.K. Dwivedi1*, Naveen Dhingra1, Poonam (Journal of Ecobiotechnology, 2010)
Abstract â€œHealth is wealthâ€, which depends on the interaction of various biotic and abiotic factors at individual, family, community, national and international level. Enduring exposure of various health hazards generated as a consequence of rapid modernization is deteriorating the health and making us ill. Additionally, the contamination in air, water and food has caused brutality in its behavior. Conditions are even more substantial in socio-economically compromised areas. Jhansi, due to considerably lesser political interest is a socio-economically backward area.Â Like many other cities of India the ambient air quality of Jhansi is also being depreciated day after day. Poor traffic control, uneven roads and extensive automobile exhausts are additionally helping in its quality drop. Certain man made pollutants e.g. O3 (produced by photochemical reaction) and other particulate matters (<10 Âµ in size) are airing the illness. Since, they can cross the innate immune barriers of human respiratory system and plays a significant role in genesis and amplification of hypersensitive allergic reactions. Various asthmatic, allergic and other respiratory effects of certain air pollutants have been reported. Chief air contaminating resource in the area is poorly maintained three wheeler automobiles emission. The ambient air quality of seven important and crowded places of city was assessed. Furthermore, the health risk assessment questionnaire (HRAQ) based survey was conducted to estimate the exposure and itâ€™s after effect on health of middle class subpopulation (activity-wise) in the area. Total 2000 individualsâ€™ data was collected and analyzed through developed In-silico tool. The outcomes are discussed here in detail in the present study. — 1Institute of Biomedical Sciences, 2Department of Zoology, Bundelkhand University, Jhansi-284128, Uttar Pradesh, India — Please Cite This Article As: Â L.K. Dwivedi, Naveen Dhingra, Poonam Sharma, Rambir Singh. 2010. Assessment of Air Pollution and its Impact on Human Health Behavior in Jhansi City, Uttar Pradesh, India. J. Ecobiotechnol. 2(4): 33-39. Â